Transience and sentimentality - Cole, Tom; Gangitano, Lia; Grunenberg, Christoph; Myles, Eileen; Rossi, Jeri Cain (Boston : ICA (The Institute of Contemporary Art), 1998)
Brattin, John ; Bright, Deborah ; Cohen, Morgan ; Cole, Tom ; Eisenberg, Cheri ; Friedman, Tom ; Gavann, Jason Byron ; Guthrie, Andrew ; Jasper, Maura ; Kauper, Kurt ; Kramer, John ; Kysor, Chris ; Levine, Saul ; Mathewson, Stephen ; Myles, Eileen ; O'Reilly, John ; Porter, Bonnie ; Price, Luther ; Puntar, Diana ; Rossi, Jeri Cain ; Subrin, Elisabeth ; Welitoff, Suara ; Westergren, Charlotta
Transience and sentimentality, ICA (The Institute of Contemporary Art) Boston, February 18 - May 24, 1998
biog. per kunstenaar p. 34-39
Engels
kunstcatalogus